Cooperative Effects of Semen and Seminal Fluid of Immunized Males on Embryo Development - Kontsevaya, G. V.; Gerlinskaya, L. A.; Moshkin, Y. M.; Anisimova, M. V.; Stanova, A. K.; Babochkina, T. I.; Moshkin, M. P. (Research Aspects in Biological Science Vol. 6, 2022)
The differential effect of spermatozoa and seminal fluid of male CD1 mice immunized with KLH antigen (keyhole limpet hemocyanin) on the development of pre- and post-implantation embryos (16 days) were studied. We show that immunization of male mice reduces the success of in vitro fertilization and the survival of embryos at the blastocyst stage. Exposure of surrogate mothers to the seminal fluid of immunized males not only eliminates the negative impact of immunization on spermatozoa, but also stimulates the growth rate of embryos due to the optimized distribution of maternal resources. These results point to possible scenarios for the impact of antigen challenge on male reproductive function, including vaccination or viral infections.